Odpowiedzi

2009-10-03T14:36:26+02:00
( 1/2 - 2/3)² - ( 7 - 25/3 ) ² = (3/6-4/6)²-(21/3-25/3)²=(-1/6)²-(-4/3)²=1/36-16/9
=1/36-64/36=-63/36=-7/4
2009-10-03T14:36:35+02:00
( 1/2 - 2/3)² - ( 7 - 25/3 ) ² =(1/4-4/9)-(49-625/9)=(9/36-8/36)-(421/9-625/9)=1/36-421/9+625/9=1/36+204/9=1/36+816/36=819/36=22 i 3/4

powyzsza odp. wojtkap jest bledna, chyba nie potrafi podniesc do kwadratu...
2009-10-03T16:21:11+02:00
( 1/2 - 2/3)² - ( 7 - 25/3 ) ²=(3/6-4/6)²-(21/3-25/3)²=(-1/6)²-(-4/3)²=1/36-16/9=1/36-64/36=(-63/36)=(-21/12=(-1i9/12)

kaen27-4/9 to nie jest 8/36, tylko 16/36, bo 9*4=36, a 4*4=16. ;p